2005
DOI: 10.1074/jbc.m413146200
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Structure and Regulation of Glucokinase from a Novel Mutation (V62M), Which Causes Maturity-onset Diabetes of the Young

Abstract: Glucokinase (GCK) serves as the pancreatic glucose sensor. Heterozygous inactivating GCK mutations cause hyperglycemia, whereas activating mutations cause hypoglycemia. We studied the GCK V62M mutation identified in two families and co-segregating with hyperglycemia to understand how this mutation resulted in reduced function. Structural modeling locates the mutation close to five naturally occurring activating mutations in the allosteric activator site of the enzyme. Recombinant glutathionyl S-transferase-V62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
109
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(119 citation statements)
references
References 43 publications
9
109
1
Order By: Relevance
“…It is possible that this mild thermal lability alone might not be sufficient to account for the hyperglycaemia observed in the patients. Loss of regulation by GCKR and allosteric activators has been reported for other GCK mutants with increased or nearly-normal enzyme activity [18,31]. Despite this, we found that the R397L mutation did not affect GCK-GCKR binding in vitro and was not located in the allosteric site predicted from the crystal structure [30].…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…It is possible that this mild thermal lability alone might not be sufficient to account for the hyperglycaemia observed in the patients. Loss of regulation by GCKR and allosteric activators has been reported for other GCK mutants with increased or nearly-normal enzyme activity [18,31]. Despite this, we found that the R397L mutation did not affect GCK-GCKR binding in vitro and was not located in the allosteric site predicted from the crystal structure [30].…”
Section: Discussionsupporting
confidence: 45%
“…Interestingly, the crystal structure of GCK complexed with a GCK allosteric activator indicates that the M235 residue, together with residues V62, I159, M210, I211 and V452, is involved in hydrophobic interactions with this compound [30]. As expected from this model, MODY2 mutations V62M and M210K result in a loss of effect of GCK activators as well as a loss of inhibition by GCKR [18,31]. It has been proposed that these effects could be responsible for the development of hyperglycaemia.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This sensor depends on mitochondrial function in addition to a number of other intermediates of the glucose-sensing pathway. Mutations in the other genes of this pathway (including those for glucokinase [GCK], KIR6.2 [KCNJ11] and SUR1 [ABCC8]) present with dysregulated insulin secretion in neonatal life [8,9].…”
mentioning
confidence: 99%